2017
DOI: 10.1515/meceng-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

An Influence of Parameters of Micro-electrical Discharge Machining on Wear of Tool Electrode

Abstract: To achieve better precision of features generated using the micro-electrical discharge machining (micro-EDM), there is a necessity to minimize the wear of the tool electrode, because a change in the dimensions of the electrode is reflected directly or indirectly on the feature. This paper presents a novel modeling and analysis approach of the tool wear in micro-EDM using a systematic statistical method exemplifying the influences of capacitance, feed rate and voltage on the tool wear ratio. The association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…While increasing the electrode rotational speed slightly improved machining time and accuracy due to better flushing conditions, very high rotational speed was found to be unsuitable for machining accuracy. In the study conducted by Puthumana et al [11] provided valuable insights into the tool wear behaviour in μ-EDM. By using statistical methods and analyzing the effects of capacitance, feed rate, and voltage on the tool wear ratio, they contributed to a better understanding of the machining process and its optimization.…”
Section: Introductionmentioning
confidence: 99%
“…While increasing the electrode rotational speed slightly improved machining time and accuracy due to better flushing conditions, very high rotational speed was found to be unsuitable for machining accuracy. In the study conducted by Puthumana et al [11] provided valuable insights into the tool wear behaviour in μ-EDM. By using statistical methods and analyzing the effects of capacitance, feed rate, and voltage on the tool wear ratio, they contributed to a better understanding of the machining process and its optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The published literature indicate that just few studies have reported on the analysis of minimizing the shape deviation in WEDM by taking into account the electrical discharge parameters [28][29][30][31][32]. Therefore, in this paper, theoretical and experimental investigation of the WEDM condition and parameters like the dielectric volumetric flow Q v , wire tension F n and wire speed on shape deviation for the cut parts was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The tool wear in micro EDM is affected by multiple factors including electric parameters, machining polarity, dielectric fluid, tool electrode shape, materials of the tool electrode and workpiece, and different EDM processes. A lot of research has been carried out on tool wear for achieving a lower wear ratio or/and compensating for the wear [3][4][5][6]. In 2015, Maradia et al found that the carbonaceous build-up on graphite tool electrodes can be obtained as electrode wear protection in meso-micro EDM.…”
Section: Introductionmentioning
confidence: 99%